1999
DOI: 10.1116/1.590748
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of AlGaAs compositions and GaAs growth at high temperature by spectroscopic ellipsometry and desorption mass spectroscopy

Abstract: Analysis of buried (Al,Ga)As interfaces after molecular-beam epitaxy overgrowthGallium desorption behavior at AlGaAs/GaAs heterointerfaces during high-temperature molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…A lot of studies on the evaporation of Al 1Àx Ga x As [31][32][33][34][35][36][37][38][39][40] have also been done. It was found that during evaporation of Al 1Àx Ga x As, the more volatile III-constituent Ga could evaporate preferentially compared to Al, and so the sample surface could be ended with AlAs.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies on the evaporation of Al 1Àx Ga x As [31][32][33][34][35][36][37][38][39][40] have also been done. It was found that during evaporation of Al 1Àx Ga x As, the more volatile III-constituent Ga could evaporate preferentially compared to Al, and so the sample surface could be ended with AlAs.…”
Section: Discussionmentioning
confidence: 99%